Morphopedological compartimentation and its applicability: a methodological approach - Castro, Selma Simões de; Salomão, Fernando Ximenes de Tavares (GEOUSP Espaço e Tempo (Online), 2000)
A concept of morphopedological compartments and a simplified methodological approach for their research is proposed, which have em phasis on their spacial délimitation and their soil's behaviour. In this paper it is considered that morphopedological compartments, which is obtained from bedrock, relief and soils relationships, are intrinsic and homogeneous environmental unities, and perfectly recognizable in middle and detailed scales. They show typical pedological Systems which is constituted by continuum superposed or juxtaposed horizons, situated along of lenght of toposequences. For their research is requested a integrated study based on successive levels of treatment to obtain the secure risk prognostics for preventive planning and land use management directed to environmental (re)equilibrium control